Future directions for inclusive teacher education : an international perspective - Forlin, Chris (London : Routledge, 2012)
"Are teachers ready for inclusion? What is appropriate teacher education? In recent years, the understanding of inclusion, which initially focused only on children with disabilities, has taken on a broader concept that aims to provide educational equity and equality of access for all students within the same regular school system. Future Directions for Inclusive Teacher Education provides a wealth of ideas about how to support teachers through positive training approaches, by sharing the writings of some of the most influential educators in the field of teacher education for inclusion. Written by a range of internationally acknowledged experts, highly experienced researchers and influential keynote speakers, together the authors provide a plethora of ideas for teacher educators to ensure that their training is pertinent, accessible, and futures-orientated. This up to date and accessible book combines three key areas related to teacher education for inclusion, which provide: - A review of what is happening across the globe by offering examples from different regions; - Preparation for teachers to support students with a range of diverse needs including poverty, ethnicity, cultural diversity, SEN, ASD, sensory impairments and those who are considered gifted and talented; A consideration of systemic approaches, policy, and partnerships, and how these can be better employed in the future. This highly topical text will support all teaching professionals and students in their transformation of inclusive teacher education"-- Provided by publisher.
pt. 1. Global perspectives on teacher education for inclusion -- pt. 2. Diversity and its challenges -- pt. 3. Future directions.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Teachers -- Training of; Inclusive education; Electronic books